Creating Future Ready Information Technology Policy for National Education Systems - Zagami, J.; Bocconi, S.; Starkey, L.; Wilson, J.; Gibson, David; Downie, J.; Malyn-Smith, J.; Elliott, S. (Springer Netherlands, 2018)
© 2018, The Author(s). With the increasing relevance of information and communication technologies (ICT) and the global transition towards the knowledge society, school systems and higher education now face increasing challenges involved in preparing students for successful participation in the knowledge society. In many countries, this is leading to manifold efforts and changes in national policies concerning ICT integration into education systems. This paper outlines four challenges concerning the design, implementation, and evaluation of national policy: (1) creating future ready policy, (2) achieving systemic perspectives in stakeholders, (3) promoting commitment to learning from policy, and (4) developing and implementing supportive processes. The paper shares an international perspective on these four major challenges and proposes strategy perspectives and solutions, as well as tactics that could be applied to advance a nation’s educational system empowered by technology.